Analisis Kemampuan Membaca Pemahaman Menggunakan Model Cooperative Integrated Reading and Composition (CIRC) - Wibowo, Sigit Ari; Juhana, Juhana; Winarni, Retno (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
The purpose of the study was to describe the planning, implementation and ability to read comprehension as well as the obstacles to learning reading comprehension through the Cooperative Integrated Reading and Composition (CIRC) method in online learning of class 2 students at SD Negeri Wonomulyo and the teacher's solutions for overcoming these obstacles. This research is a qualitative research. This type of descriptive qualitative research used in the form of research with case studies (case study). The population in this study were all 22 (twenty two) grade 2 students at SD Negeri Wonomulyo Wonogiri. Data collection techniques with observation, interviews and documentation. Data analysis techniques with qualitative descriptions. The results showed that the initial step taken by the teacher in preparing a reading comprehension lesson plan was to determine the identification of learning materials, followed by developing a lesson plan. Planning learning to read comprehension using the CIRC method with the consideration that the CIRC method students will obtain information repeatedly through reading, responding, and presenting activities. The implementation of learning to read comprehension through the CIRC method is carried out in two ways, namely through online and limited face-to-face. Learning reading comprehension activities using the CIRC method are carried out in 6 (six) stages, namely the preliminary stage (orientation), the organizational stage, the core stage of introducing concepts, exploration and application stages, publication stages, and closing stages, strengthening, and reflection. The ability to read comprehension can be assessed from several abilities, namely: capturing the contents of the reading, summarizing the reading, answering questions based on the content of the reading, retelling the contents of the reading. The results of daily tests show that by using the CIRC method most students can achieve learning mastery. The high learning outcomes of reading comprehension are caused by using CIRC, students obtain information repeatedly. The obstacles to learning reading comprehension in grade 2 SDS Negeri Wonomulyo through the CIRC method are learning environment factors, student intellectual factors, and psychological and physiological factors